2018
DOI: 10.1155/2018/5919743
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Adjustment Problem and Its Predictors among First-Year Undergraduate Students in Ethiopian University: A Cross-Sectional Institution Based Study

Abstract: Background Being in a university for the first time is an unpleasant event and time of heavy pressure relating to social things and dissatisfaction for several new faculty students. Adjustment difficulties are the foremost common issues among freshman students; World Health Organization area unit researched a full-of-life adjustment innovation in universities. Despite this reality, there is a few literature that identifies prevalence and factors related to the adjustment downside among university/college stude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 16 publications
3
10
0
1
Order By: Relevance
“…This finding is compatible with findings from other studies conducted in Iran and Ethiopia, showing that students feel less lonely as they go through the semesters (15,16). According to research findings from Ethiopia, first-year students had problems adjusting themselves to the new environment (26). The research performed at the University of Washington by English et al supported these findings and indicated that attending universities increases the students' potential to experience loneliness (27).…”
Section: Description Of Sample Characteristicssupporting
confidence: 87%
“…This finding is compatible with findings from other studies conducted in Iran and Ethiopia, showing that students feel less lonely as they go through the semesters (15,16). According to research findings from Ethiopia, first-year students had problems adjusting themselves to the new environment (26). The research performed at the University of Washington by English et al supported these findings and indicated that attending universities increases the students' potential to experience loneliness (27).…”
Section: Description Of Sample Characteristicssupporting
confidence: 87%
“…The transition from high school to university represents a life phase characterized by various personal, social, and academic shifts. All of these changes require adaptation, and they may be particularly stressful for students who are asked to regulate themselves to handle the demands of the new academic and social environment [ 7 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some freshmen are able to deal with these transitional challenges and adjust to university life successfully, whereas others feel overwhelmed and experience various adjustment problems leading them to drop out of university [ 7 , 8 ]. Adjustment to college has been considered as an important factor in predicting university outcomes in terms of grades, retention, withdrawal, or success [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mental disturbances and other unhealthy states are common in lonely individuals [19]. Freshman students had problems to adjust themselves into new environment as evidenced in University students at Dila, Ethiopia [20]. Cultural backgrounds affect loneliness which may increase loneliness in some and decreases in others [21].…”
Section: Introductionmentioning
confidence: 99%